Konstrukcia planovaneho rodicovstva v obdobi statneho socializmu v byvalom Ceskoslovensku - Potancokova, Michalela (Gender, Equal Opportunities, Research, 2007)
The analysis deals with the discourse on family planning and contraception in the former Czechoslovakia during the 1970s and 1980s. Family planning became a topic at the beginning of the 1970s, nearly 30 years after the legalisation of the liberal abortion law. Induced abortion was introduced without any public discussion and before the introduction and spreading of effective contraception. Family planning was understood mainly as limitation of the family size to desired number of children. Although the timing of conception is also mentioned, in reality it was not possible due to problematic access of young women to effective contraception. Instead of promoting contraception, experts propagated abstaining from sexual intercourse in order to limit the risk of unwanted pregnancy, induced abortion and lowering age at sexual debut. Contraception was seen as a potential threat to traditional sexual norms, which institutionalised sexuality into marriage and made a double moral eligible. Low use of modern contraception has to be seen in the light of its difficult accessibility, a lack of information, low quality of especially hormonal contraceptives and attitudes of gynaecologists inhibiting the use of intrauterine and hormonal contraception among single childless and young women, since it was perceived as a risk to their fertility and a means of spreading promiscuity. In terms of ideology, contraception was seen as a threat to population growth
Keywords: Family planning; Attitudes towards contraception; Pre-1989 Czechoslovakia